Information Brokers and Reference Services, 1st edition - Kinder, Robin (Routledge, 2020)
The contradictory yet complementary relationship between libraries and information brokers is examined in this volume, first published in 1988. Since its escalation in the 1960s, information brokering has challenged the role of the library in society. Librarians discuss their concerns about information brokers - the impact of brokers on reference services, the competence of brokers, abuse of library services by brokers, and whether libraries should provide competing fee-based services. Brokers share their own view as ‘entrepreneurs’, providing background, offering advice, and explaining the risks involved in their business. This lively, often controversial discussion offers suggestions for improving relations between libraries and information brokers, while continuing to serve the public well.